DINAMIKA QIRA’ATOLOGI: MENELAAH PERBEDAAN QIRAAH MUTAWATIR DAN SYADZ SERTA PANDANGAN ULAMA TENTANG RUKUNNYA - Soim, Moh; Aziz, Fatih Abdul (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2024)
This study examines the complexity of mutawatir and shadz qiraah and its implications for contemporary Qur'anic studies. Against the backdrop of debates about the validity of qiraah and its potential contribution to Qur'anic interpretation, this study aims to analyze the differences between mutawatir and shadz qiraah and explore scholarly views on the pillars of qiraah. Using a qualitative method with a critical-analytical approach, the study examines classical and contemporary literature and evaluates the implications of qiraah for tafsir, Islamic law and modern linguistic studies. The results show that while mutawatir qiraah is generally accepted, there are complex nuances in the application of its validity criteria. Qiraah shadz, although not used in worship, has significant value in the development of Qur'anic tafsir and linguistics. This study reveals the potential of qiraah in enriching the understanding of the miracles of the Qur'an, including in the scientific aspect (kauniyyah). This study contributes to a deeper understanding of the dynamics of qiraah science and its relevance to contemporary Qur'anic studies, paving the way for the integration of classical and modern perspectives in Qur'anic studies.